Rumen fermentation parameters and papillae development in Simmental growing bulls with divergent residual feed intake - Romanzin, A.; Braidot, M.; Beraldo, P.; Spanghero, M. (Animal (Cambridge, England), 2024)
•Residual feed intake is an attractive trait for the livestock sector.•Residual feed intake affects propionate production but not methane.•A small part of ruminal bacteria differs between the feed efficiency groups.•Macroscopic changes in ruminal papillae morphology were observed.•The main causes of animal feed efficiency differences remain unknown. Residual feed intake (RFI), a widespread index used to measure animal feed efficiency, is influenced by various individual biological factors related to inter-animal variation that need to be assessed. Herein, 30 Simmental bulls, raised under the same farm conditions, were divided on the basis of RFI values into a high efficient group (HE, RFI =  − 1.18 ± 0.33 kg DM/d, n = 15) and a low efficient group (LE, RFI = 0.92 ± 0.35 kg DM/d, n = 15). Subsequently, bulls were slaughtered at an average BW of 734 ± 39.4 kg. Their ruminal fermentation traits were analysed immediately after slaughtering and after 24 h of in vitro incubation. Furthermore, ruminal micro-biota composition and ruminal papillae morphology were examined. The LE group exhibited a higher propionate concentration as a percentage of total volatile fatty acids (17.3 vs 16.1%, P = 0.04) in the rumen fluid collected during slaughtering, which was also confirmed after in vitro fermentation (16.6 vs 15.4% respectively for LE and HE, P = 0.01). This phenomenon resulted in a significant alteration in the acetate−to−propionate ratio (A:P) with higher values for the HE group, both after slaughter (4.01 vs 3.66, P = 0.02) and after in vitro incubation (3.78 vs 3.66, P = 0.02). Methane production was similar in both groups either as absolute production (227 vs 218 mL for HE and LE, respectively) or expressed as a percentage of total gas (approximately 22%). Even if significant differences (P < 0.20) in the relative abundance of some bacterial genera were observed for the two RFI groups, no significant variations were observed in the alpha (Shannon index) and beta (Bray–Curtis index) diversity. Considering the papillae morphology, the LE subjects have shown higher length values (6.26 vs 4.90 mm, P < 0.01) while HE subjects have demonstrated higher papillae density (46.4 vs 40.5 n/cm2, P = 0.02). Histo-morphometric analysis did not reveal appreciable modifications in the total papilla thickness, boundaries or surface between the experimental groups. In conclusion, our results contribute to efforts to analyse the factors affecting feed efficiency at the ruminal level. Propionate production, papillae morphology and a few bacterial genera certainly play a role in this regard, although not a decisive one.